44. EFFECTS OF SUPPLEMENTING HANIE KID 1+ ON NUTRITIONAL STATUS AND HEALTH OF 12-24 MONTH OLD CHILDREN (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of nutritional Hanie Kid 1+ product supplementation on nutritional status and health of 12-24 months old children.Subject and methods: The intervention study with a control group. Sample size: 60 children aged 12-24 months for each groups. The intervention group supplementing Hanie Kid 1+ twice a day for 2 months, and the control group with a regular diet. The study was completed in Ninh Binh in February 2024. The tool is calibrated and applies techniques standards for identifying the nutritional, health status and avoiding bias in research. Analyze data by SPSS20.0 software and describe by ratios and averages, use of appropriate statistical tools in biomedical research.Results: The intervention group there was the rate of respiratory infection was lower 48.3% (5.0% vs. 53.3%) (p < 0.05); the rate of diarrhea was lower 36.7% (3.3% vs. 40.0%) (p < 0.05); the rate of constipation was lower 16.7% (0.0% vs. 16.7%); the rate of anorexia was lower 43.3% (6.7% vs. 50.0%) (p < 0.05). Weight was higher 0.58 kg (0.94 ± 0.11kg vs. 0.36 ± 0.17 kg) (p < 0.05). Average of height was higher 0.54cm (1.08 ± 0.29 cm vs. 0.54 ± 0.25 cm) (p < 0.05). The rate of underweight malnutrition reduced 31.7% (p < 0,05); stunting reduced 15.0% (p < 0,05). There was no overweight or obesity.Conclusion: Supplementing of Hanie Kid 1+ product for 2 months improved the immune system and reduced respiratory infection, improved digestion, weight, height and reduce the malnutrition better than those of the control group (p < 0,05).
Keywords: Micronutrients; formula milk; height; weight; preschool children.